An annotated checklist of the South African Acanthodrilidae (Oligochaeta: Acanthodrilidae: Acanthodrilinae, Benhamiinae) - Plisko, Jadwiga Danuta (Zootaxa, 2012)
A checklist of acanthodrilid species known from South African biotopes is here compiled from the literature and theunpublished KwaZulu-Natal Museum database of Oligochaeta (NMSAD). Most species belong to one of the twosubfamilies, Acanthodrilinae, with a total of 107 valid indigenous species and 17 subspecies, belonging to five genera(Chilota, Eodriloides, Microscolex, Parachilota, Udeina). Furthermore, eight peregrine species of Microscolex(Acanthodrilinae) and Dichogaster (Diplothecodrilus) (Benhamiinae) are included. One of them, Dichogaster(Diplothecodrilus) austeni Beddard, 1901 may occur naturally in north-eastern South Africa. For all recorded species thetype localities and known records in South Africa are given. Additional environmental data, when available, are included.The present location of most of the type material is indicated. Five species of Udeina are transferred to Parachilota:Udeina avesicula, U. hogsbackensis, U. septentrionalis, U. pickfordia Lungström, 1968 and U. transvaalensis Lungström,1972, now Parachilota avesiculus, P. hogsbackensis, P. septentrionalis, P. pickfordius, and P. transvaalensis, respectively.Dubious or uncertain genera and species are listed separately, including Hegesipyle Kinberg, 1867 and its only species H.hanno, the first acanthodrilid species recorded from South Africa. Valid species names, synonyms and doubtful species are arranged alphabetically.